ANALISIS STRUKTURALISME TERHADAP NOVEL KAU, AKU DAN SEPUCUK ANGPAU MERAH - Andi Tabbu Sassak (Department of Sociology, Faculty of Social and Political Sciences, Sriwijaya University, 2021)
This research aimed to apply Roland Barthes structuralism and Paul Ricoeur hermeneutic theories into the novels Kau, Aku dan Sepucuk Angpau Merah (KADSAM). The method used in this study was a qualitative descriptive with the utilization of a phenomenology research strategy and the unit of analysis in KADSAM novels. Secondary data were obtained from the books, journals, and research report related. Data examined and analysis were using validity and reability techniques. In data analysing was using structuralism. The result of this research were describing multiple lexia’s data, analysis using Barthes code and Roland Barthes’s two other signification. In the KADSAM novel were built five main sign up that are angpau merah, sepit, pelampung, Pontianak and Surabaya. Based on strucrural analysis could be expressed a narrative structure text of the story wich founded a connotative sign that had other means as myth. Myth was present in people’s daily lives. Based on structural analysis could be expressed a narrative structure text of the story which was founded a connotative sign that had other means as myth. Myth was present in people’s daily lives. Based on hermeneutic analysis, the relation of myth and connotative sign were known as a new meanings of communication, modernization and culturalization that was KADSAM novel wanted to tell